Incidence and predictors of chronic kidney disease among patients with diabetes treated at governmental hospitals of Harari Region, eastern Ethiopia, 2022 - Cheru, Abera; Edessa, Dumessa; Regassa, Lemma Demissie; Gobena, Tesfaye (Frontiers in Public Health, 2024)
Chronic kidney disease (CKD) is the leading cause of morbidity and mortality in diabetic patients. ;However limited evidence is available about its incidence and predictors in Ethiopia, specifically in Harari region.A retrospective follow-up study was conducted among 520 diabetes patients between September 1, 2012, to May 30, 2022, and followed their treatment in governmental hospitals of the Harari region.The risk of developing Chronic Kidney Disease was calculated with 95% CI, and the risk was stratified by type of Diabetes mellitusand Predictors of Chronic Kidney Disease were determined using the Gompertz regression model with the baseline Cox model. Data from 494 patients were included in the final analysis with 26 (5%) excluded.. 51 (10.32%) developed Chronic Kidney Disease over the 10 years follow up period with an incidence rate of 2.16 cases (95% CI 1.64-2.84) per 100 person-years of observation. The risk of Chronic Kidney Disease among patients older than 60 years was increased by three times (AHR: 3.09, 45 95% CI: 1.56, 6.14) and by more than three times (AHR: 3.53, 95% CI: 1.43, 8.71) among patients with Diabetes Mellitus for longer than 5 years of stay with the Diabetes Mellitus. Moreover, increase by four folds among patients with high-density lipoprotein cholesterol (HDL-C) level < 40 mg/dl (AHR: 3.84, 95% CI, 1.80-8.18) and those with positive baseline proteinuria (AHR:3.77,95% CI: 1.43-8.71). We found that one-in-ten diabetic patients had developed Chronic Kidney Disease within ten years of the Diabetes Mellitus diagnosis. Advanced age, longer duration of diabetes, lower baseline High density lipoprotein-cholestrollevel and proteinuria had increased the hazards of developing Chronic Kidney Disease. We recommend a more focused follow-up of elderly patients with advanced disease status at baseline for the optimal control of the Diabetes Mellitus that prevents its furthering to Chronic Kidney Disease.